Reaction time trends in the women's sprint and hurdle events at the 2004 Olympic Games - Babic, V.; Delalija, A. (New Studies in Athletics, 2009)
Reaction time values, though very small, can differentiate overall performance results in sprint races, where the margin of victory is often measured in thousandths of a second. The purpose of this research was to study the reaction time characteristics for the athletes competing in the women's sprint and hurdles events at the 2004 Olympic Games in Athens and to determine differences between events and between the competitive levels of the athletes. The sample of 250 female athletes was selected from the list of competitors and divided by event and by how far the athletes advanced in their competitions (qualification rounds, semi-finals and finals), which defined their competitive level. The results showed statistically significant differences between the events, confirming the findings of earlier studies. Although no statistically significant differences between the competitive levels were found in most of the events, certain differences were established in the 100m, 400m and 100m hurdles. In the 100m and 400m, the differences showed a negative trend, while the 100m hurdles showed a positive trend. Based an these findings, reaction time can be considered as one of the possible determinants of athletes' competitive quality. In a separate article, the results presented here are compared to those of the male participants at the Games.